2013
DOI: 10.5194/acp-13-3463-2013
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of aged Asian dust particles by the combined use of quantitative ED-EPMA and ATR-FTIR imaging

Abstract: Abstract. In our previous works, it was demonstrated that the combined use of quantitative energy-dispersive electron probe X-ray microanalysis (ED-EPMA), which is also known as low-Z particle EPMA, and attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) imaging has great potential for a detailed characterization of individual aerosol particles. In this study, extensively chemically modified (aged) individual Asian dust particles collected during an Asian dust storm event on 11 Nove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 84 publications
1
27
0
Order By: Relevance
“…The peak at ~1115 cm −1 (peak b) was attributed to sulphate groups as in CaSO 4 , corroborating the crystalline phase detected by XRD in Fig. 7a [60]. At higher temperatures (1100 °C), the peaks observed in the region of 800–1100 cm −1 were attributed to the silicate tetrahedral vibration commonly observed for wollastonite [57].…”
Section: Resultssupporting
confidence: 74%
“…The peak at ~1115 cm −1 (peak b) was attributed to sulphate groups as in CaSO 4 , corroborating the crystalline phase detected by XRD in Fig. 7a [60]. At higher temperatures (1100 °C), the peaks observed in the region of 800–1100 cm −1 were attributed to the silicate tetrahedral vibration commonly observed for wollastonite [57].…”
Section: Resultssupporting
confidence: 74%
“…Recently, Prather et al (2013) successfully revealed size resolved associations between inorganic and organic species within individual sea spray aerosols (i.e., chemical mixing state), covering two orders of magnitude in size from 30 nm to 3 mm, by integrating the results from several single particle techniques, including ATOFMS, STXM, and TEM. For the same particles on the substrate, the combined use of quantitative electron probe X-ray microanalysis (EPMA) with n aerosol mass spectrometer total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) imaging and Roman microspectrometry (RMS) were successfully applied to characterize the complex internal structure and physicochemical properties of the same ensemble of Asian dust particles (Sobanska et al, 2012;Song et al, 2013). NanoSIMS combined with TEM can determine even better the mixing state of organic aerosols in individual particles (e.g., Fig.…”
Section: Combination Of Different Single Particle Technologiesmentioning
confidence: 99%
“…The Gobi desert of northern China and Mongolia and the Taklamakan desert of western China are the major source regions of East Asian dust (McNaughton et al, 2009;Mochida et al, 2007). Modeling results indicate that around 100−460 Tg yr −1 of dust is emitted annually from the East Asia source regions (Laurent et al, 2006) and transported eastwardly, exerting a significant impact on the atmosphere over the downwind regions, including eastern coastal China (Arimoto et al, 2006;Kim et al, 2004;Li et al, 2014;Li and Shao, 2009;Sun et al, 2010;, Korea (Geng et al, 2014;Song et al, 2013;Sullivian et al, 2007), Japan (Takahashi et al, 2011;Tobo et al, 2010;Uno et al, 2009) and western North America (Huebert et al, 2003;Leaitch et al, 2009;McNaughton et al, 2009;Parrington et al, 1983;Singh et al, 2009). A recent study found that dust from the Sahara and Asia is transported over the Pacific Ocean and increases the snow precipitation in mountainous areas of Nevada, USA (Creamean et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the chemical affinity of nitrogen oxides and nitric acid with dust particles (Hanisch and Crowley, 2001;Mogili et al, 2006;Saliba and Chamseddine, 2012;Song et al, 2013;Usher et al, 2003), such a change in the atmospheric environment of China suggests that dust particle behavior might also be changing compared to the situations 10 years ago. Therefore, it is necessary to investigate the present physicochemical properties of airborne particles in the country during dusty periods.…”
Section: Introductionmentioning
confidence: 99%